2000
DOI: 10.1002/1521-4095(200010)12:19<1448::aid-adma1448>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Polymethacrylate-Silica Hybrid Nanoporous Materials: A Bridge Between Inorganic and Polymeric Molecular Sieves

Abstract: Mesoporosity combined with organic polymer functionality and hydrophobicity could give rise to promising new materials with applications in host–guest chemistry and biosensor devices. The synthesis of polymer–silica hybrid mesoporous materials with pore sizes of 3–6 nm is described, in which materials with large specific surface areas (∼800 m2 g–1) and pore volumes (∼0.7 cm3 g–1) as well as relatively narrow pore size distributions are produced by a sol‐gel reaction in the presence of a non‐surfactant template… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…In this scheme, R = alkyl groups, R 0 = methacryloxy group and X = R or H. The T i (i = 1, 3) and Q j (j = 1, 4) species in this reaction scheme are classified in Table 1. flexibility and abrasion resistance. 3-(Trimethoxysilyl)propyl methacrylate (MPTMA), also referred to in abbreviated form in the literature as c-MPS [5], TPM [14], MSMA [10,15,16] and MEMO [17,18], was used both as a secondary inorganic source and a silane coupling agent to act as a compatibilizer to improve adhesion between the inorganic phase and organic resin [5,18]. A schematic reaction sequence for these organic-inorganic hybrid materials using TEOS and MPTMA as inorganic precursors is shown in Fig.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this scheme, R = alkyl groups, R 0 = methacryloxy group and X = R or H. The T i (i = 1, 3) and Q j (j = 1, 4) species in this reaction scheme are classified in Table 1. flexibility and abrasion resistance. 3-(Trimethoxysilyl)propyl methacrylate (MPTMA), also referred to in abbreviated form in the literature as c-MPS [5], TPM [14], MSMA [10,15,16] and MEMO [17,18], was used both as a secondary inorganic source and a silane coupling agent to act as a compatibilizer to improve adhesion between the inorganic phase and organic resin [5,18]. A schematic reaction sequence for these organic-inorganic hybrid materials using TEOS and MPTMA as inorganic precursors is shown in Fig.…”
Section: Introductionsupporting
confidence: 87%
“…The inorganic phase is mostly obtained from metal alkoxides via hydrolysis and condensation reactions in the sol-gel process. Tetraethoxysilane (TEOS) is commonly used as a precursor of silica in this process [3][4][5][6][7][8][9][10][11][12]. In the study we report here, four different hybrid coating materials of silica and urethane acrylate with various organic-inorganic ratios were prepared using sol-gel methods following the Vitresyn Ò process [13] in order to determine how altering the proportions of the organic and inorganic materials in the starting composition affects the thermal properties and the chemical interaction mechanisms of the resultant hybrid systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wei et al reported a non-surfactant-templating pathway to synthesize the disordered mesoporous (i.e., wormporeslike) materials [18,19]. The synthesis of mesoporous silica is carried out by HCl-catalyzed hydrolysis and polycondensation of tetraethyl orthosilicate (TEOS) in the presence of nonsurfactant organic compounds, including dibenzoyltartaric acid, D-glucose, and D-maltose, acting as the pore-forming agents, which can be removed by solvent extraction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The preparation of these polymer composites is as versatile as the used materials themselves. [6][7][8][9][10][11][12][13][14][15] For example, polymerizations can be carried out in the presence of layered silicates like montmorillonite. Depending on the reaction conditions, either intercalated or exfoliated composites can be obtained.…”
Section: Introductionmentioning
confidence: 99%